War beyond words languages of remembrance from the Great War to the present - Winter, Jay 1945- (Cambridge University Press, 2017)
What we know of war is always mediated knowledge and feeling. We need lenses to filter out some of its blinding, terrifying light. These lenses are not fixed; they change over time, and Jay Winter's panoramic history of war and memory offers an unprecedented study of transformations in our imaginings of war, from 1914 to the present. He reveals the ways in which different creative arts have framed our meditations on war, from painting and sculpture to photography, film and poetry, and ultimately to silence, as a language of memory in its own right. He shows how these highly mediated images of war, in turn, circulate through language to constitute our 'cultural memory' of war. This is a major contribution to our understanding of the diverse ways in which men and women have wrestled with the intractable task of conveying what twentieth-century wars meant to them and mean to us
Keywords: Geschichte 1914-2017; Gesellschaft; Weltkrieg (1914-1918); War in art; World War, 1914-1918; Collective memory / Social aspects; Kollektives Gedächtnis; Krieg